Effects of Tin, Antimony and Molybdenum in Mn-W-O /Ir1-x-ySnyO2+0.5y/Ti Anodes for Oxygen Evolution in Seawater Electrolysis - Bhattarai, Jagadeesh (Scientific World, 2010)
An attempt was made to enhance the oxygen evolution efficiency in seawater electrolysis by the addition of tin, antimony and molybdenum to Mn-W oxide electrocatalysts prepared by anodic deposition on the intermediate Ir1-x-ySnyO2+0.5y/Ti electrode. Ir1-x-ySnyO2+0.5y/Ti supported nanocrystalline γ-MnO2 type Mn-W-X-O(X=Sn,Sb,Mo) electrocatalysts with grain size of about 5-11 nm were tailored by anodic deposition. All the examined Mn-W-X(X=Sn,Sb,Mo)- O anodes showed the almost 100% oxygen evolution efficiency at 1000 A.m-2 in 0.5 M NaCl solution of pH 1 at 25°C. They guaranteed the stable anode performance of about 99.75-99.85% oxygen evolution efficiencies for more than five months. Keywords: Global warming; CO2 recycling; Oxygen evolution anode; Seawater electrolysis; Hydrogen production electrode. DOI: 10.3126/sw.v8i8.3844 Scientific World Vol.8(8) 2010 pp.39-43